2004
DOI: 10.1590/s0004-28032004000300002
|View full text |Cite
|
Sign up to set email alerts
|

O uso de nutrição enteral precoce pós-transplante hepático adulto

Abstract: Early enteral nutrition is an effective method in the provision of calories and safe in application to patients undergoing orthotopic liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Regarding nutritional states, this study demonstrated a high PCM prevalence, especially through HGS. Other studies have shown this method to be the most sensitive method for PCM diagnosis in such a population (1,4,5,6,29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding nutritional states, this study demonstrated a high PCM prevalence, especially through HGS. Other studies have shown this method to be the most sensitive method for PCM diagnosis in such a population (1,4,5,6,29) .…”
Section: Discussionmentioning
confidence: 99%
“…AMC was calculated using the following formula: AMC = AC -(TSF x 0.314). HGS measurement used the dynamometry technique (4) and a 1 kgf graded Baseline ® dynamometer with a 100 kgf capacity, a clock indicator, and a maximum reading pointer. Three measurements were taken from each patient, and the greatest value was used.…”
Section: Methodsmentioning
confidence: 99%
“…No Brasil, a aplicação da ANSG tem mostrado correlação significativa de alguns dados com a avaliação objetiva (74,75,76,77) . Vaz et al (77) encontraram correlação entre a avaliação objetiva e subjetiva e maior tempo de hospitalização.…”
Section: Avaliação Nutricionalunclassified